2018
DOI: 10.14256/jce.2080.2017
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical properties and bearing capacity of blast furnace slag

Abstract: Geotechnical characterization and bearing capacity performance of blast furnace slag Geotechnical properties and factors affecting bearing capacity of Blast Furnace Slag (BFS) are analysed in this study. The California Bearing Ratio (CBR) tests were performed using fine and coarse grained BFS samples. The CBR test samples were prepared using standard and modified compaction energies. To examine the effect of pore fluid on bearing capacity, samples were prepared with tap and sea water. Test results show that fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The internal friction angle of BFS is 39 • -43 • , and the specific gravity ranges between 2.29 and 3.35 [12,33,34]. The results of CBR tests on GGBFS revealed that the bearing capacity affects the soil arrangement and interparticle forces such as matric suction and dilatancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal friction angle of BFS is 39 • -43 • , and the specific gravity ranges between 2.29 and 3.35 [12,33,34]. The results of CBR tests on GGBFS revealed that the bearing capacity affects the soil arrangement and interparticle forces such as matric suction and dilatancy.…”
Section: Introductionmentioning
confidence: 99%
“…The results of CBR tests on GGBFS revealed that the bearing capacity affects the soil arrangement and interparticle forces such as matric suction and dilatancy. The CBR ranges between 65% to 160% for the standard and modified Proctor compaction techniques [34].…”
Section: Introductionmentioning
confidence: 99%